2011
DOI: 10.1136/jnnp.2010.224261
|View full text |Cite
|
Sign up to set email alerts
|

Visual extinction in relation to visuospatial neglect after right-hemispheric stroke: quantitative assessment and statistical lesion-symptom mapping

Abstract: Background Visual neglect and extinction are two common neurological syndromes in patients with righthemispheric brain damage. Whether and how these two syndromes are associated or share common neural substrates is still a matter of debate. Methods To address these issues, the authors investigated 56 patients with right-hemispheric stroke with a novel diagnostic test to detect extinction and neglect. In this computerised task, subjects had to respond to target stimuli in uni-and bilateral stimulation condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 44 publications
2
71
0
Order By: Relevance
“…The unilateral condition probes target detection in the absence of competition and potential effects are therefore conceptually closer to spatial neglect. Even though visual extinction and spatial neglect are dissociable in clinical populations, there is a large co-occurrence of the two syndromes (Vossel et al, 2011). In fact, there is hardly any evidence that TMS can induce clear-cut cases of extinction, that is, disruption of bilateral but intact unilateral stimulus detection, in healthy volunteers.…”
Section: Visual Extinctionmentioning
confidence: 98%
“…The unilateral condition probes target detection in the absence of competition and potential effects are therefore conceptually closer to spatial neglect. Even though visual extinction and spatial neglect are dissociable in clinical populations, there is a large co-occurrence of the two syndromes (Vossel et al, 2011). In fact, there is hardly any evidence that TMS can induce clear-cut cases of extinction, that is, disruption of bilateral but intact unilateral stimulus detection, in healthy volunteers.…”
Section: Visual Extinctionmentioning
confidence: 98%
“…To comprehensively assess (spatial) inattention, it is important to use multiple attention tests (Saj, Verdon, Vocat, & Vuilleumier, 2012;Verdon, Schwartz, Lovblad, Hauert, & Vuilleumier, 2010). Therefore, we used the line bisection test that is supposed to be sensitive to posterior lesions (at least for contralesional inattention: (Rorden, FuhrmannBerger, & Karnath, 2006;Weiss et al, 2000) as well as cancellation tests that are also affected by frontal lesions (Vossel et al, 2011). To further increase the sensitivity of our neuropsychological assessment (especially for ipsilesional and non-lateralized attention deficits), only cancellation tests with distractors were used in the current test battery (Weintraub & Mesulam, 1988).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Recent studies found a double dissociation between neglect and extinction, suggesting that these two conditions may reflect separate dysfunctions (Umarova et al, 2011;Vossel et al, 2011;Pavlovskaya, Soroker, & Bonneh, 2007;Bonneh, Pavlovskaya, Ring, & Soroker, 2004;Karnath, Himmelbach, & Küker, 2003; for a review, see de Haan, Karnath, & Driver, 2012).…”
Section: Introductionmentioning
confidence: 98%